What is it all but luminous [compact disc, unabridged] : notes from an underground man - Garfunkel, Art (Random House Audio, 2017)
Traces the author's experiences before, during, and after Simon & Garfunkel, from his youth in the mid-twentieth century and early successes with Paul Simon to the heyday of their popularity and the gradual divides that ended their partnership.